Heptanuclear Disk‐Like MII3LnIII4 (M = Ni, Co) Coordination Clusters: Synthesis, Structures and Magnetic Properties. Issue 33 (7th September 2017) - Griffiths, Kieran; Harding, Chris; Dokorou, Vasiliki N.; Loukopoulos, Edward; Sampani, Stavroula I.; Abdul‐Sada, Alaa; Tizzard, Graham J.; Coles, Simon J.; Lorusso, Giulia; Evangelisti, Marco; Escuer, Albert; Kostakis, George E.
Abstract : The synthesis, characterization, crystal structures and magnetic properties of isoskeletal heptanuclear disk‐like M II 3 Ln III 4 coordination clusters with the general formula [Co II 3 Ln III 4 (µ3 ‐OH)6 L6 (CF3 SO3 )][(CF3 SO3 )5 ] where Ln = Gd (2 ), Y (3 ) and [Ni II 3 Ln III 4 (µ3 ‐OH)6 L6 (CF3 SO3 )][(CF3 SO3 )5 ] where Ln = Dy (4 ), Gd (5 ), Y (6 ) are presented. All the compounds are stable in solution as confirmed by ESI‐MS. Magnetic studies were performed for compounds2, 4, 5 and6 and indicate ferromagnetic coupling while the magnetocaloric properties of5 are characterized by Δ S m = –15.4 J kg –1 K –1 at T = 5.0 K and Δ T ad = 5.9 K at T = 2.3 K, for µ0 Δ H = 7 T. Abstract : The use of a monoanionic Schiff Base ligand in 3d/4f chemistry yields a family of heptanuclear M II 3 Ln III 4 (M = Ni, Co) disk‐like coordination clusters. The Ni II /Ln III analogues represent the first examples bearing this disk‐like topology. Magnetic studies reveal a dominant ferromagnetic coupling, while the Ni II 3 Gd III 4 analogue5 shows magnetocaloric properties at liquid‐helium temperatures.